Relação entre condutividade elétrica e desempenho fisiológio de sementes de arroz - Ascoli, Carla Aparecida (2019)
The quality of a seed is defined as a set of characteristics that establish its value for sowing, considering the interaction between the physical, genetic, physiological and health attributes. The objective of this study was to determine its physiological potential and to correlate with the vigor, germination and viability tests with the electrical conductivity test of 3 varieties of rice (ANA 8001, ANa 9005 CL and ANa 9027). The experiment was carried out in the 2017/18 crops, in the production area of the company Agro Norte Pesquisa e Sementes (ANPS) of Sinop / MT, as well as the tests conducted in the internal seed analysis laboratory. Seeds of rice (Oryza sativa L.) of the cultivars ANa 8001, ANa 9005 CL and ANa 9027 were randomly selected from 9 lots (3 lots per cultivar). The seeds were produced in the 2017/18 harvest, with planting date for the cultivar ANa 8001 on 12/16/17 and a cycle of 112 days, with the geographical coordinates of the production field 10.56 ° S and 55.03 ° W and for cultivars ANa 9005 CL and ANa 9027 on 11/11/17 both with 115 days cycle, geographical coordinates of the production field 11.44 ° S and 55.31 ° W. The moisture content and the first germination, standard germination, sand emergence, tetrazolium and accelerated aging tests followed the methodology described by Brazil (2009) with changes, for the accelerated aging the vigor responses were determined at eight temperatures (34, 38, 42, 43, 44, 45, 46 and 50 °C). For the soaking curve the seeds were weighed initially and at pre-defined periods (2, 4, 6, 8, 10, 12, 24, 36, 48, 60 and 72 h) until the radicle emergence and for the electrical conductivity curve, two factors of luminosity (absence and presence of light (photoperiod with 8 h)) were evaluated, under the temperature of 25 ± 1 oC with 9 soaking periods (4, 8, 12, 16, 20, 24, 32, 40 and 48 h). A completely randomized design was used for all the evaluations. In the vigor parameter the ANA 9027 variety presents an average of 69%, being statistically below the other varieties ANa 8001 (79.54%) and ANa 9005 CL (84.41%), the same behavior is found in both the direct germination tests, indirect tests of viability. The 3 rice cultivars studied follow the same water absorption pattern, and it is verified that the water content absorbed from the beginning of the hydration process and reached by the rice seeds at the end of the process, with 72 h is affected by the physiological quality and that less vigorous seeds present lower rate of hydration and final moisture. The same trend of the imbibition curve is observed in the electrical conductivity curve, that is, the leachate release follows the same water absorption pattern, The same tendency of the imbibition curve is observed in the electrical conductivity curve, that is, the leachate release follows the same water absorption pattern, it is highlighted that the electric conductivity test can be used to determine the seed vigor of rice. From the methodologies tested, in the investigation of the physiological quality of the seeds, for the electrical conductivity test the best response was obtained with the imbibition stage performed in the absence of light (without photoperiod), being possible to reduce the period of immersion of the seeds to 8 h in order to differentiate the physiological potential of rice seeds above 80% of vigor, from those below this standard.